2009
DOI: 10.1111/j.1600-0560.2008.01014.x
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic neuromas of the penis: a clinical, histopathological and immunohistochemical study of 17 cases

Abstract: We present 17 penile traumatic neuromas. The mean patient age at presentation was 38 years (range 23-59 years). The most common site involved was the penile shaft. The lesions ranged from 1 to 7 mm in greatest dimension. The clinical diagnosis in all cases included condyloma acuminatum. In all cases, a history of trauma because of prior biopsy and/or circumcision was found. Histologically, all lesions showed similar features consisting of an increased number of dermal nerve bundles embedded within a fibrous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…A case series study in 2009 by Salcedo et al 3 reported that traumatic neuromas are caused by circumcision or biopsies. The case of a 23-year-old man reported in 2009 by Marinho and Bouscarat 8 also was a traumatic neuroma secondary to circumcision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A case series study in 2009 by Salcedo et al 3 reported that traumatic neuromas are caused by circumcision or biopsies. The case of a 23-year-old man reported in 2009 by Marinho and Bouscarat 8 also was a traumatic neuroma secondary to circumcision.…”
Section: Discussionmentioning
confidence: 99%
“…It forms a nodular proliferation arising from the hyperplasia of axons and nerve sheaths after nerve injury or resection 1, 2, 3. Traumatic neuroma is a disorganized growth of the proximal portion of an injured or resected nerve; it can occur in any lesion, but few have been reported in the penis 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The ultimate etiopathology is theorized to be nerve amputation with disorganized attempt at regeneration. These locations include oral mucosa after surgical enhancements, sites of tooth extraction, and in the region of a previous circumcision.…”
Section: Subungal Traumatic Neuromamentioning
confidence: 99%
“…1 Traumatic neuromas can occur at any site where injury has occurred, resulting in the disorganized growth of the damaged proximal nerve as it fails to reconnect with the distal nerve sheath. 3 In histopathological findings, traumatic neuroma has been found to consist of peripheral nerve fiber proliferating to form variable-sized nerve fascicles in an irregularly arranged pattern. It is well circumscribed by surrounding fibrous tissue.…”
Section: Multiple Traumatic Neuromas After Laser Ablation Treatment Fmentioning
confidence: 99%